Prognostic Problems of the Public and Power Organization of the Russian Society: Archetypes and Sociocultural Basis of Functioning and Development - Mamychev, Alexey Y.; Lyubashits, Valentin Y.; Shalyapin, Sergey O.; Filippova, Maria K. (International Review of Management and Marketing, 2016)
The modern prognostics appeals to the analysis of the archetypic bases, which are the cornerstone of sociocultural basis of the society public and power organization, that is, according to the authors, the base for construction and evolutionary development of the socio-political and right cultural environment in any society. The author's concept is based on the basis of the multidimensional analysis of evolution as public process, with inclusion of discussion of the accident and regularity philosophical questions as the defining factors of stable reproduction of public and imperious interaction in society. The need to foretell the future was aware of all times. However, especially great need for projections is in the XXI century with its rapid pace of social development. Now social changes happen more often, and objectively before the person there is a need to find ways of adaptation to changes which already arose and which would be, but till certain time are still unknown. The work content observes the difference, relationship and interaction between the archetypes and related socio-cultural phenomena. Keywords: archetype, archetypic structures, state, culture, right, public and power organization JEL Classifications: D71, H55, K49